Inclusive Political Intersections of Migration, Race, Gender and Sexuality – The Cases of Austria and Denmark. Issue 1 (2nd January 2020) - Sauer, Birgit; Siim, Birte
ABSTRACT: The article aims to integrate key concepts from social movement, citizenship and gender theories with afocus on (political) intersectionality at the interface of migration, race, gender and sexuality. It explores the responses from civil society groups to the exclusive intersections of right-wing politics and discourses in Austria and Denmark with afocus on inclusive intersectionality and transversal politics. The article asks if and how the intersectional repertoires of NGOs were able to create transversal politics and joint activities and explains why these NGOs were unable to counter right-wing hegemony. It uses the cases of Austria and Denmark to illustrate the diverse mobilizations of counter-forces against the attempts to forge an anti-migration and anti-Muslim consensus. The focus is on the mobilization of anti-racist and pro-migrant groups, comparing their strategies and inclusionary repertoires including feminist claims, the framing of activist citizenship, acts of citizenship and of solidarity. The article scrutinizes strategies of transversal politics against the exclusionary right in the two countries; shows the influence of the different contexts of civil society mobilization, political cultures, welfare and gender regimes as well as the differences between right-wing forces in the two countries.